Works programme for rural development in Bangladesh and the issue of accountability - Mashreque, M Shairul; Quddus, S. M. Abdul (The Academy for Planning and Development, 1994)
This paper attempts to examine the problems associated with implementation of works programme. Our purpose is to see wether the elements of participatory rural development are present in the works programme. We ought to figure out the difficulties encountered the practical operation that render attempts at participatory development all but futile. It is not wrong to assume that a modicum of beneficieries' participation would ensure a good measure of accountability. Hence the issue of accountability would featured promionently in the present study.